2015
DOI: 10.1016/j.ejcdt.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Augmented alternative communication methods in intubated COPD patients: Does it make difference

Abstract: Background: Intubated patients experience an intensified need to communicate while their ability to do so is compromised as the endotracheal tube prevents speech which creates patient agitation.Aim: To determine the impact of using augmented alternative communication methods on outcome of intubated COPD patients.Patients and methods: Sixty male COPD intubated patients at the pulmonary critical care unit Mansoura University hospital were randomly assigned into two groups of 30 patients for each. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 14 publications
3
41
0
3
Order By: Relevance
“…Findings of the present study is consistent with the study done by El-Soussi AH et al 9 which shows the majority of study subjects in the study group (63.3%) evaluated communication methods used by the researcher as ""extremely helpful"" and indicated that alternative communication methods can improve the level of satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of the present study is consistent with the study done by El-Soussi AH et al 9 which shows the majority of study subjects in the study group (63.3%) evaluated communication methods used by the researcher as ""extremely helpful"" and indicated that alternative communication methods can improve the level of satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…It appears that communication aids can be helpful for both patients and health care personnel alike in the ICU setting when patients are conscious, alert and on mechanical ventilation. The intervention studies we examined showed increased patient satisfaction (Otuzoglu et al ., 2013; El‐Soussi et al, ; Rathi and Baskaran, 2014; Rodriguez et al, ), reduced frustration (Rodriguez et al, ), increased health care personnel knowledge (Happ et al, ) and increased understanding between patients and health care personnel (Maringelli et al, ; Happ et al, ). The studies aiming to test communication aids used a variety of instruments to measure the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo realizado no Hospital Universitário de Mansoura, no Egito, em uma Unidade de Terapia Intensiva, indicou que o uso da prancha de comunicação, por pacientes intubados, foi um recurso efetivo para diminuir o estresse, favorecer a comunicação e aumentar o grau de satisfação dessas pessoas em relação ao cuidado em saúde oferecido (EL-SOUSSI et al, 2015).…”
Section: Introductionunclassified
“…Entretanto, esses estudos têm focalizado a dificuldade comunicativa em clínicas específicas (MOTA; FABIANA, 2010; CERANTOLA; HAPP, 2012); as dificuldades comunicativas associadas ao uso da traqueostomia (RODRIGUEZ; BLISCHAK, 2010); a utilização de um único recurso de CAA, como as pranchas impressas (EL-SOUSSI et al, 2015) ou o tablet (PALMEIRAS; BETTINELLI; PASQUALOTTI, 2013). Além de serem estudos em que a indicação do recurso de CAA é feita sem levar em consideração a preferência do usuário ( VAN DER MEER et al, 2011;IACONO et al, 2013;PATERSON;CARPENTER, 2015).…”
Section: Introductionunclassified